“My Own Old English Friends”: Networking Anglican Settler Colonialism at the Shingwauk Home, Huron College, and Western University - Cross, Natalie; Peace, Thomas (Historical Studies in Education / Revue d'histoire de l'éducation, 2021)
Focusing on Huron College, Shingwauk Residential School, and Western University, this article considers how common social and financial networks were instrumental in each institution’s beginnings. Across the Atlantic, these schools facilitated the development of networks that brought together settlers, the British, and a handful of Indigenous individuals for the purposes of building a new society on Haudenosaunee and Anishinaabe Land. Looking specifically at the activities of Huron’s principal, Isaac Hellmuth, and Shingwauk’s principal, Rev. Edward F. Wilson, the article demonstrates how ideas about empire, Christian benevolence, and resettlement entwined themselves in the institutions these men created. Specifically, Anglican fundraising in both Canada and England reinforced the importance of financial networks, but also drew upon and crafted an Indigenous presence within these processes. Analyzing the people, places, and ideologies that connected Huron, Western, and Shingwauk demonstrates how residential schools and post-secondary education were ideologically—and financially—part of a similar, if not common, project. As such, the article provides a starting point for considering how divergent colonial systems of schooling were intertwined to serve the developing settler-colonial project in late nineteenth-century Ontario. En se concentrant sur le Collège universitaire Huron, le pensionnat Shingwauk et l’Université Western, cet article examine le rôle-clé que les réseaux sociaux et financiers communs ont joué aux origines de chacune de ces institutions. De l’autre côté de l’Atlantique, ces écoles ont facilité le développement de réseaux qui rassemblaient les colons, les Britanniques et les individus autochtones sélectionnés pour fonder une nouvelle société sur les territoires Haudenosaunee et Anishinaabe. En étudiant plus spécifiquement les activités du directeur du Collège universitaire Huron, Isaac Hellmutth, et du directeur du pensionnat Shingwauk, le révérend Edward F. Wilson, l’article démontre comment ...